2019
DOI: 10.3390/ijerph17010041
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Symptoms and Lung Function among Ethiopian Women in Relation to Household Fuel Use

Abstract: Exposure to household air pollution has been linked to chronic obstructive pulmonary disease, respiratory symptoms and reduced lung function. This study aims to assess respiratory symptoms and lung function among Ethiopian women in relation to exposure to HAP. We conducted a cross-sectional study among non-smoking women responsible for household cooking. Data was collected on socio-demographic characteristics, respiratory symptoms and risk factors using a validated questionnaire. Spirometry with reversibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 41 publications
1
25
2
2
Order By: Relevance
“…IAP is a less studied subject in Ethiopia, and synthesizing available evidence in the literature is very challenging owing to the evidence quality and heterogeneity. Several studies have found a link between biomass fuel use and acute respiratory infections, asthma, chronic obstructive pulmonary disease, and tuberculosis in Ethiopian households ( Andarge et al., 2021 ; Balidemaj et al., 2021 ; Desalegn et al., 2011 ; Downward et al., 2018 ; Mengesha et al., 2004 ; Tamire et al., 2020 ; Andualem et al., 2020 ). According to a study conducted in Gondor, the prevalence of respiratory symptoms among women was 46.1% [95% CI: 42.6 %–49.7 %], with a runny nose, shortness of breath, and phlegm accounting for 32.07 %, 15.03 %, and 12.63 %, respectively ( Andualem et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…IAP is a less studied subject in Ethiopia, and synthesizing available evidence in the literature is very challenging owing to the evidence quality and heterogeneity. Several studies have found a link between biomass fuel use and acute respiratory infections, asthma, chronic obstructive pulmonary disease, and tuberculosis in Ethiopian households ( Andarge et al., 2021 ; Balidemaj et al., 2021 ; Desalegn et al., 2011 ; Downward et al., 2018 ; Mengesha et al., 2004 ; Tamire et al., 2020 ; Andualem et al., 2020 ). According to a study conducted in Gondor, the prevalence of respiratory symptoms among women was 46.1% [95% CI: 42.6 %–49.7 %], with a runny nose, shortness of breath, and phlegm accounting for 32.07 %, 15.03 %, and 12.63 %, respectively ( Andualem et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a growing body of literature (WHO, 2015;Sigsgaard et al, 2015;Hystad et al, 2019;Tamire et al, 2019) , 2010). Its effect is strictly related to the toxic compounds attached to the particle surface, since toxic compounds such as PAHs and dioxins/furans, heavy metals may be easily carried into the lungs (Stabile et al, 2018).…”
Section: Analysis Of the Environmental And Health Risks From The Extended Use Of Biomass Burningmentioning
confidence: 99%
“…Only two of the participants had exposure to tobacco smoke: one former smoker and the other because of environmental tobacco exposure. Given the low prevalence of tobacco smoking in the country, further research into other risk factors for COPD, including the use of biomass fuel, is indicated (7,21). Meanwhile, health promotion and protective measures in the community and in the workplaces should be initiated.…”
Section: Social and Religiousmentioning
confidence: 99%